FINANCIAL PERFORMANCE ANALYSIS OF COMPANIES THROUGH LIQUIDITY AND PROFITABILITY RATIO APPROACHES - Putri, PA Andiena Nindya; Djaniar, Upik; Lumentah, Natalia Reyne; Mutmainah, Mutmainah; Mere, Klemens (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This article presents a comprehensive literature review on the financial performance analysis of companies through liquidity and profitability ratio approaches. Financial performance is a critical indicator of a company's overall health and sustainability, influencing investment decisions and stakeholder confidence. Liquidity ratios, such as the current ratio and quick ratio, assess a company's ability to meet its short-term obligations, providing insights into operational efficiency and cash management. On the other hand, profitability ratios, including return on assets (ROA) and return on equity (ROE), measure a company's ability to generate profit relative to its revenue, assets, and equity. This review synthesizes recent studies to highlight the interrelation between liquidity and profitability, emphasizing that strong liquidity positions often correlate with improved profitability metrics. The findings underscore the importance of both ratios in providing a holistic view of a company's financial performance, enabling managers and investors to make informed decisions. Furthermore, the article suggests areas for future research, particularly regarding the impact of external factors on these financial ratios.